The Development of Fruit and Vegetal Probiotic Beverages Using Lactiplantibacillus pentosus LPG1 from Table Olives - Azahara Lopez-Toledano; Lourdes Moyano; Francisco Noé Arroyo-López; Paola Martinez-Merina; Diego Bohoyo-Gil; Veronica Romero-Gil; Virginia Martin-Arranz; M. Angeles Varo (Applied Sciences)
Plant-based foods can be an alternative to dairy products as a source of probiotic microorganisms, especially aimed at lactose-intolerant people. In this work, four new formulations based on the mixture of fruits and vegetables with the addition of a unique probiotic strain (Lactiplantibacillus pentosus LPG1) obtained from the olive industry were developed. Moreover, the nutritional profile, antioxidant activity, and organoleptic characteristics of the beverages produced were studied. The results showed that it is possible to reach an average probiotic count of 6.45 log10 CFU/mL at 52 days of storage at 4 °C without the presence of Enterobacteriaceae, fungi/molds, or Staphylococcus, Listeria, or Salmonella spp. On the other hand, the beverages developed could be classified as high-value-added functional beverages due to their high antioxidant capacity of up to 33% DPPH inhibition, considerable total polyphenol content higher than 0.5 g gallic acid/L, and adequate nutritional composition. Additionally, sensory analysis via flash profile, acceptance, and affective test revealed that all probiotic beverages were appropriate in terms of odor, taste, and color, rendering them market ready to drink.